(untitled) (Oshada, 2025)
Magnetic Resonance Imaging (MRI) is a radiological imaging modality that does not use ionizing radiation, but it often causes anxiety. This anxiety is triggered by the relatively long examination duration, ranging from 30 to 45 minutes, and is triggered by the examination environment, which is shaped like a tunnel, which can trigger claustrophobia. One method that can be used to reduce anxiety is through complementary therapies, such as lavender aromatherapy, which is known to have a relaxing effect. This study aims to determine the effect of lavender aromatherapy on reducing anxiety levels in patients undergoing MRI examinations at the Radiology Installation of RSI Siti Rahmah Padang. The study design used was a quasi-experimental study with a pre-test and post-test with a control group design. The number of research samples was 54 people who were divided into two groups, namely the control group and the intervention group. The intervention group was given lavender aromatherapy before undergoing MRI examination, while the control group was not given any treatment. Anxiety levels were measured using the Magnetic Resonance Imaging-Anxiety Questionnaire (MRI-AQ) before and after the intervention of using Lavender aromatherapy. The results showed a significant decrease in patient anxiety levels in the intervention group after being given lavender aromatherapy (p-value = 0.001). Meanwhile, the control group did not show a significant change in anxiety levels (p-value > 0.05). Lavender aromatherapy is effective in reducing anxiety levels in patients undergoing MRI examinations. This study suggests that lavender aromatherapy can be considered as a complementary method to reduce patient anxiety in the MRI room, thereby improving the comfort and quality of radiology services in hospitals.